2020
DOI: 10.3390/ijerph17238781
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with In-Hospital Mortality after Continuous Renal Replacement Therapy for Critically Ill Patients: A Systematic Review and Meta-Analysis

Abstract: Continuous renal replacement therapy (CRRT) is a broadly-accepted treatment for critically ill patients with acute kidney injury to optimize fluid and electrolyte management. Despite intensive dialysis care, there is a high mortality rate among these patients. There is uncertainty regarding the factors associated with in-hospital mortality among patients requiring CRRT. This review evaluates how various risk factors influence the in-hospital mortality of critically ill patients who require CRRT. Five databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…The potential explanation was that the risk of mortality from myocardial infarction was very high, masking the effect of serum ALB; several studies indicated that patients with AKIN stage 2 who had CRRT could not improve their prognosis ( 1 , 26 ), which may be the reason why serum ALB did not affect the prognosis of patients with myocardial infarction and AKIN stage 2 undergoing CRRT in this study. Studies had also shown that hyperkalemia, oliguria, or anuria were not related to patient mortality, which was similar to the findings of this research ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 91%
“…The potential explanation was that the risk of mortality from myocardial infarction was very high, masking the effect of serum ALB; several studies indicated that patients with AKIN stage 2 who had CRRT could not improve their prognosis ( 1 , 26 ), which may be the reason why serum ALB did not affect the prognosis of patients with myocardial infarction and AKIN stage 2 undergoing CRRT in this study. Studies had also shown that hyperkalemia, oliguria, or anuria were not related to patient mortality, which was similar to the findings of this research ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 91%
“…The predictors of in-hospital mortality in patients with AHF undergoing CRRT have been reported to include older age, lower SBP and DBP, and a decreased serum creatinine level (22), which is consistent with our research. We found that age was an undoubtedly hazardous factor for AHF in that the older the patient, the higher the mortality rate, which is consistent with previous research (23).…”
Section: Discussionsupporting
confidence: 92%
“…CRRT is a primary life-support technique used to maintain hemodynamic stability and aid in renal recovery in ICU patients [ 18 ]. However, higher mortality rates, ranging from 40% to 70%, have been reported in patients receiving CRRT [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%